Children’s Environmental Health Experience and Interest Among Pediatric Care Providers in Vietnam - Nancy J. Beaudet, MS, CIH; Garry C. Alcedo; Quan C. Nguyen, MD; Dan Jacoby, PhD; Quynh Kieu, MD; Catherine J Karr, MD, MS, PhD (Journal of Health and Pollution, 2011)
Background. In rapidly developing regions of the world such as Southeast Asia, marked industrialization with insufficient regulation places children at increased risk for significant environmental exposures. Health care providers have a key role in identifying, treating and preventing environmentally-related illnesses. Objectives. The authors undertook a survey of pediatric health care providers in Vietnam in order to gain preliminary insight into environmental hazard knowledge, and attitudes and beliefs regarding the relative importance of environmental factors in child health that could guide future initiatives towards building up capacity for children’s environmental health in the region. Methods. A formal written and self-administered survey instrument was adapted from the World Health Organization’s Children’s Environmental Health Survey and translated into Vietnamese. The survey was administered via convenience sampling after formal introduction to children’s environmental health (CEH) was made through lectures or meetings with pediatric care providers affiliated with the major children’s hospitals and pediatric departments in Vietnam. Results. One hundred forty-one pediatric care providers completed the survey. Most indicated environmental factors are considered to be very important in child health (84%); 98% felt the magnitude of the problem is increasing; and air pollution is seen as the top environmental health issue facing the country. The most commonly identified problems in their clinical experience included: food poisoning due to microbiological agents (85%); pesticide poisoning (77%); tobacco smoke exposure (75%); and inadequate sanitation (60%). Although most (80%) endorsed asking about children’s environmental conditions in clinical practice, a little more than a third (39%) were confident taking an environmental exposure history. For most key topics, less than half had received specific training. A majority (63%) of survey respondents were very interested in more environmental health training. Conclusions. Pediatric health care providers in Vietnam believe that environmental hazards in child health is an important topic that is routinely encountered in their care of patients, but training, experience and self-efficacy in these topics are limited. Financial Disclosure. None reported